Factors Related to the Completeness of Basic Immunization for Infants at Oinlasi Health Center, South Amanatun District, South Central Timor Regency - Taneo, Sefrida Yunarsa; Radja Riwu, Yuli; Boeky, Daniela (Timorese Journal of Public Health, 2024)
Immunization is a program from the government that is given to protect the immune system in the child's body so that later the child is not susceptible to infectious diseases, even if the child is sick he only has a mild illness. The purpose of this study was to determine what factors were related to the completeness of basic immunization for infants at the Oinlasi Health Center, Amanatun Selatan District, Timor Tengah Selatan Regency. In this study using a quantitative type with a cross sectional approach. The population in this study were all mothers who had children aged 10 months-2 years as many as 396 people. The research sample was 80 people. Samples were taken using random sampling method. Data were collected from direct interviews with respondents using questionnaires and books on Maternal and Child Health (KIA) from each child. The data in this study were analyzed using the Chi-Square test with a value of 0,05, to see the relationship between variables. In accordance with the results of the analysis conducted in this study, it can be shown that there are variables that have a significant relationship with the completeness of providing basic immunization to infants, including mother's knowledge (p = 0,002), distance from home to immunization site (p = 0,004), and support family (p=0,003), while the variable that did not have a significant relationship with the completeness of basic infant immunization was the mother's attitude (p=1,000). Mother's knowledge, distance from home to the place of immunization, and support from family members are factors that have a relationship with the completeness of basic immunization in infants in this study. pregnant women about immunization is very good and important for children, so that later basic immunizations are complete and children do not get sick easily.